Autenticidade e educação em Charles Taylor - Foschiera, Rogério (2008)
I analyse the Taylor perspective of the authenticity through a hermeneutics of his main works to propose the meaning of educating in the authenticity as of Charles Taylor. With moral authenticity and ontology Taylor presents an anthropology anchored in the morals and in the ontology. The perspective of the authenticity supposes an integral vision of the human being, a paidéia (formation), a look that considers the objective elements constituent of the human being and that need the objective science to be treated, but inserted in a more ample vision and that guards the human and social phenomenon in a rich language. To educate in the authenticity is to implement a new reading of oneself and a new posture in the educative activity. He who educates the human is the human. Only the human builds the human. With authenticity and epistemology one perceives that the perspective of the authenticity does not exclude the scientific paradigm, but needs other paradigms, mainly the hermeneutics. With the hermeneutics it is possible, under the Taylor optics, to save the human and social phenomena. The formative references of parents, teachers and citizens must be revised, as our epoch tends to valorize and put stress on what is exactly scientific, useful, technique, objective, rational and material, not taking care of, or devaluating subjective, affective, valuable and transcendental elements. With authenticity and language I evidence Taylor's comprehension about the nature of the language and the emphasis he gives to the definition of the human being as "animal bearer of logos", as well as the meaning and the derivations of the expressive perspective. In authenticity and politics I point out that modernity came to stay and with it some social-politic instances as the economy of market, the political sphere, the democracy and liberty. Problematic questions are stressed, mainly linked to the individualism and to the possibilities of manipulation. In this the demand for recognition and the necessary opening to the multiculturalism grow. Two politics: the one of the rights of equality for all and the one of the recognition of the differences are integrated in the Taylor perspective of the authenticity. Necessarily, the human being, to be authentic, will be in constant reference to horizons of a sense that they transcend the individual, is what I present with authenticity and transcendence. Taylor situates the question with the stress of the homo religious (religious man), reconfiguring it as of the personal experience and in an opening to the pluralism.